PENGARUH PENYAJIAN, AKSESIBILITAS, DAN KUALITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PELAPORAN KEUANGAN PERUSAHAAN PADA SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Rini Dewi Sahputri; Baru Harahap; Ferdila Ferdila; Maya Richmayati; Khadijah Khadijah (JURNAL AKUNTANSI BARELANG, 2026)
ABSTRACT This study aims to examiine the effect of financial statement presentation,accessibility, and quality on financial reporting accountability in transportation sector  companies during 2020–2024. A quantitative approach was applied using secondary data from annual financial reports selected through purposive sampling. Variables were measured through content analysis with interval scales covering presentation completeness, ease of access, information quality, and accountability indicators. The data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression with the assistance of SPSS version 25. The results indicate that, in general, companies demonstrate fairly good levels of presentation, accessibility, quality, and accountability, although variations still occur across firms and periods. Partially and simultaneously, financial statement quality appears to be the strongest factor in explaining accountability, followed by presentation and accessibility. These findings highlight the importance of information openness, accessible reporting, and high-quality financial information in strengthening stakeholder trust and corporate accountability practices Keywords: Accountability, Presentation, Accessibility, and Quality in the Transportation Sector